EFFECT OF THE RECTUS SHEATH BLOCK ON HEMODYNAMIC CHANGES IN TOTAL ABDOMINAL HYSTERECTOMY AS A PART OF MULTIMODAL ANESTESIA - Mitreski, Goran; Sholjakova, Marija; Laban Gucheva, Nevenka; Izairi, Pranvera; Mitreska, Valentina (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Background: Total abdominal hysterectomy (TAH) is associated with substantial postoperative pain and discomfort. Rectus sheath block (RSB) is used to block the sensory nerves of the anterior abdominal wall and thereby contribute to pain relief after lower abdominal surgeries. Aim of Study: The aim of this study is to evaluate the effect of bilateral Ultrasound (US)-guided RSB on hemodynamic changes after TAH. Patients and Methods: This prospective randomized study was carried out on 10 females, ASA I or II, presented for elective TAH under general anesthesia (GA) and randomly classified into 2 equal groups R and C of 5 patients each; patients in Group R received RSB with 40 ml ropivacaine 0.375% (20ml each side) before surgery and standard endotracheal anesthesia and patients in Group C received only standard general endotracheal anesthesia. Mean arterial Blood pressure (MAP) and Heart rate (HR) were measured as baseline, after induction of GA, every 15 min till end of surgery, immediately after recovery, at 6h, 12h and 24 h postoperatively. Conclusion: Patients in group R with bilateral US-guided RSB and standard general anesthesia had higher values of systolic and diastolic blood pressure, mean arterial pressure, and heart rate at the start and during the hysterectomy, compared to the control group C, which had a calm hemodynamic initial course. Postoperative measurements showed stable parameters, with a decrease in hemodynamic values in group R compared to group C, demonstrating an approximation to the values of group C. Key Words : hemodynamic changes, Rectus Sheath Block, Total Abdominal Hysterectomy